Clinical safety of intrauterine infusion of a uterine sanitizer in mares - Segabinazzi, Lorenzo [UNESP]; Lisboa, Fernando P; Zutter, Bruna [UNESP] (Elsevier, 2025)
BACKGROUND: Limited response to conventional therapies and rising antibiotic resistance emphasize the need for alternative treatments for infectious endometritis. A recent in vitro study showed promising antimicrobial activity of a commercial uterine cleaning sanitizer (UCS) against endometritis pathogens. However, its safety and efficacy in mares remain untested. AIMS/OBJECTIVES: This study aimed to assess the clinical safety of intrauterine infusion of UCS in reproductively sound mares. METHODS: Exp. 1. Six healthy mares with endometrial biopsies classified as I or IIA had two intrauterine infusions of UCS performed during estrus. Biopsies were taken 3 days post-treatment and 8- and 21-days post-ovulation. Exp. 2. Eleven reproductive sound mares had two estrous cycles randomly assigned to receive two intrauterine infusions of UCS or placebo (lactate ringer) at the beginning of estrus. Mares were inseminated 24 h after the last treatment. Embryo flushing was performed 8 days post-ovulation. RESULTS: Exp. 1. There was a slight change in endometrial biopsy scores, primarily due to an increased inflammatory infiltrate in the endometrium, three days post-treatment with complete recovery to baselines at 8- and 21-days post-ovulation. Exp. 2. Embryo recovery rates were similar between UCS (9/11) and placebo (8/11) cycles. CONCLUSION: In conclusion, intrauterine infusion of UCS appears to be a safe therapy in broodmare practice and may offer a promising adjuvant therapy for endometritis in mares.